2010
DOI: 10.1017/s0007114510000097
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with medium-chain TAG has long-lasting cognition-enhancing effects in aged dogs

Abstract: The present study focused on the hypothesis that dietary supplementation with medium-chain TAG (MCT) will improve cognitive function in aged dogs by providing the brain with energy in the form of ketones. Aged Beagle dogs were subjected to a baseline battery of cognitive tests, which were used to establish cognitively equivalent control or treatment groups. The dogs in the treatment group were maintained on a diet supplemented with 5·5 % MCT. After an initial wash-in period, all the dogs were tested with a bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 27 publications
3
84
1
3
Order By: Relevance
“…One promising candidate would be a lipid, rather than a carbohydrate. Medium-chain triglycerides (MCTs) are a type of saturated fat that is digested rapidly in the liver and activates the vagus nerve (Bach and Babayan, 1982), and the chronic consumption of MCTs appears to have neuroprotective effects on canine (and human) executive function (Pan et al, 2010;Reger et al, 2004). Like glucose, this energy substrate can be metabolized into a form that can be transported across the blood brain barrier (i.e., ketones).…”
Section: Discussionmentioning
confidence: 99%
“…One promising candidate would be a lipid, rather than a carbohydrate. Medium-chain triglycerides (MCTs) are a type of saturated fat that is digested rapidly in the liver and activates the vagus nerve (Bach and Babayan, 1982), and the chronic consumption of MCTs appears to have neuroprotective effects on canine (and human) executive function (Pan et al, 2010;Reger et al, 2004). Like glucose, this energy substrate can be metabolized into a form that can be transported across the blood brain barrier (i.e., ketones).…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Medium-chain triglycerides are also proved to enhance brain function in dogs and humans. 46 A recent study in middle-aged and older cats found a combination of fish oil, antioxidants, arginine, and key B vitamins successfully enhanced brain functions. 42 A deficiency of these nutrients, especially omega-3 fatty acids and B vitamins, is a proved risk factor for brain aging, stroke, and dementia in humans.…”
Section: Therapeutic Nutrition For Specific Conditions Feline Cognitimentioning
confidence: 99%
“…Furthermore, a potential cure may have been identified, as indicated by the discovery that dietary supplementation with medium-chain triglycerides resulted in long-lasting cognition-enhancing effects in aged dogs (Pan et al, 2010).…”
Section: The Selection Of the Second Speciesmentioning
confidence: 99%